KIEVAN RUS’ BETWEEN EURASIA AND EAST-CENTRAL EUROPE. RUSSIAN IDENTITY NARRATIVES FROM WEST VIEWPOINT - van Nieukerken, Arent (Porównania, 2015)
After the annexation of the Crimea by Vladimir Putin’s Russia attempts at an ideological justification of Greater Russia’s role as a dominating power in Eastern Europe have acquired a new relevance. An important issue from this point of view is the relationship between Kievan Rus’ – traditionally considered the cradle of the [Rus-sian civilization – and the Grand Principality of Moscow that replaced it after the Mongol incur-sions. Russian identity narratives usually marginalize the current status of (the) Ukraine and stress its peripherality in the “Russian world”. In order to achieve this they employ both theo-logical, cultural and geopolitical arguments that sometimes appear to be at odds with each other. Moscow is both the center of the true (orthodox) Christian faith and the civilization of the Eura-sian geopolitical space. In the latter case the Russian capital rules a multi-religious empire. Eurasian ideologues like L.N. Gumiliov and particularly Alexander Dugin reject alternative, “Western” interpretation of Russian (and Ukrainian) history by pointing out that there exists an unbridgeable gap between the Western and the Russian (or Eurasian) civilization. According to them, Western scholars can never grasp the specificity of the Russian (Eurasian) historical devel-opment. It could be argued that this argument for a relativism along civilizational lines dimin-ishes the universal impact of Christianity which (that) in the Russian context loses much of its transcendent sense and becomes – instead – a cultural feature. On the other hand, though, the (half-conscious) culturalization of orthodox Christianity gives more weight to geopolitical arguments in favor of Moscow as the center of the Russian World (and Russia as the center of Eurasia). However, this does not mean that the pivotal role of Moscow as the residence of the All Russian Patriarchate, the “legitimate” successor to the ancient metropolis of Kievan Rus’, is not exploited, in order to discredit Ukraine’s ambitions of becoming an independent state.